An Empirical Analysis of the Relationship between Unemployment and Theft Crimes - Maddah, Majid (International Journal of Economics and Financial Issues, 2012)
The purpose of this study is to examine the effect of unemployment rate on theft crimes among the provinces of Iran. This study covered the annual data from 1997 to 2006 by using of GMM method. Results have shown that there is a strong significant and positive relationship between unemployment and theft crimes in various categories. Other factors such as poverty and demographic characteristics influence on people’s motivation to crime commitment of theft. Results from estimation of crime models demonstrated that there is a significant and positive relationship between unemployment rate and theft in Iran. In fact, to fight theft crimes, government have to use policies that cause reducing the unemployment rate in society. Keywords: Unemployment; Crime; Iran JEL Classifications: E24; K42